Influence of Profile, Education Level, and Business Scale on Productivity of Business Actors in the Coconut Sugar Production Process in Lojejer Village, Wuluhan District - Wijayanti, Fifin; Rujito, Hari; Nugroho, Wendy Triadji (Politeknik Negeri Jember, 2024)
This study reveals the effect profile business, educational level and scale of the productivity of coconut sugar farm businesses is to analyze the factors affecting the production process on the productivity of coconut sugar farm businesses. In this study reveals the influence of the factors profiles of business, education, and business scale either jointly or partially, and include also the dominant factors that influence the productivity of coconut sugar farm businesses, particularly businesses coconut sugar Lojejer village, Wuluhan district. The analytical tools used in this research is the analysis of multiple linear regression. Overall the results of this study it can be concluded that the factors profiles of business, education level, and scale simultaneously affect the productivity of coconut sugar farm businesses. Partially, profile entrepreneurs, business scale, while the level of education have a significant effect on productivity is insignificant coconut sugar farm businesses. For the dominant factors affecting the productivity of farm businesses palms sugar is the profile of entrepreneurs.